Visco-Elastic Analysis of the Femur-Implant System by Using Finite Element Approach - Piszczatowski, S.; Skalski, K. (Engineering Transactions, 2015)
The subject of this work is to elucidate the significance of theological processes taking place in a bone-implant system when the implanted joint is bearing a load. The processes of mathematical modelling (by variational formulation and finite element approach) and computer-aided strength analysis of a human hip joint endoprosthesis-femoral bone system, taking into account the rheological properties of bone tissue, are presented. The three distinct types of material that are present in the system (cortical bone, trabecular bone and implant) exhibit significant differences in their elastic and rheological properties. The analysis is carried out using the finite element method. Consideration of the rheological properties of bone tissue during the analysis makes it possible to observe, under conditions of fixed loads, the changes in the fields of stresses, strains and strain energy density in the bone — implant system.